1967
DOI: 10.1007/bf02532119
|View full text |Cite
|
Sign up to set email alerts
|

The phospholipid composition of plasma in various mammalian species

Abstract: Plasma phospholipids in several common mammalian species, including cat, cow, dog, goat, guinea pig, horse, pig, rabbit, rat, and sheep, were analyzed by using chromatographic and spectrophotometric methods. Lipids were extracted from plasma with chloroform-methanol 2ratio1 (v/v) and freed of nonlipid material by passage through a Sephadex column. The phospholipids were separated by two-dimensional thin-layer chromatography (TLC). Spots were identified by spray reagents, also by infrared spectrophotometry. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 32 publications
2
48
0
Order By: Relevance
“…As reported by this laboratory previously [35], albumin may be capable of protecting LDL from degradation via scavenger-dependent pathways by properties distinct to its funtion as antioxidant. Moreover albumin, besides its ability to bind lysophospholipids [36][37][38] and its antioxidant properties [39], has multiple binding sites for fatty acids [40,41]. This may further favor the scavenging of acidic peroxidation products and macrophages, capable of incorporating albuminbound fatty acids [42], may contribute to neutralizing reactive 0 CH2--O--(CH2)ls--CH3 acidic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by this laboratory previously [35], albumin may be capable of protecting LDL from degradation via scavenger-dependent pathways by properties distinct to its funtion as antioxidant. Moreover albumin, besides its ability to bind lysophospholipids [36][37][38] and its antioxidant properties [39], has multiple binding sites for fatty acids [40,41]. This may further favor the scavenging of acidic peroxidation products and macrophages, capable of incorporating albuminbound fatty acids [42], may contribute to neutralizing reactive 0 CH2--O--(CH2)ls--CH3 acidic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The choline-containing phospholipids sphingomyelin (SM), phosphatidylcholine (PC), and lysophosphatidylcholine (lyso-PC) are the three major phospholipids found in humans [1]. These molecules comprise the major outer surface phospholipids of cell membranes and are also the major phospholipids of plasma lipoproteins [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although inter-species differences in blood composition are relatively small (Nelson 1972;Nelson 1967), partition coefficients have been found to vary with changes in hematocrit and blood lipids (Fiserova-Bergerova 1983;Lin et al 2002). There is considerable variation in reported blood-air partition coefficients of a chemical between studies as indicated by 90% confidence intervals in Figure 1.…”
Section: Blood-air Partition Coefficientsmentioning
confidence: 99%